Polymer Nanocomposites: Synthesis and Physical Properties - Yurkov, Gleb Yu.; Fionov, Alexandr S.; Popkov, Oleg V.; Kosobudskii, Igor D.; Taratanov, Nikolay A.; Potemkina, Olga V. (IntechOpen, 2011)
None